BIAS PATRIARKHI DALAM PRAKTIK POLIGINI DI KALANGAN DA’I PERSPEKTIF TAFSIR MAQASHIDI - Hafadzah, Ahmad Sona (EL-MAQRA', 2024)
The issue of polygyny is still controversial not only among the public, but also among Da'i, Ulama, Mufassir from classical to contemporary. This research will examine the patriarchal bias in the practice of polygyny which is widely narrated by Da'i circles. This study aims to analyze more objectively the verses about polygyny in the Qur'an using the maqasidi interpretation paradigm approach as a method of interpretation (as methodology) to further review the relationship between the interpretation of polygynous verses and the maqasid al-syari' principle. ah and maqashid al-qur'an and reveal maqashid behind polygynous verses that have been understood in society. The results of this study indicate that this verse has only reached the initial stage of interpretation where the ultimate goal or main maqasid of the verse is contained in the value of justice.